ANALYSIS OF THE MAIN TYPES OF ENERGY STORAGE SYSTEMS AND PROSPECTS FOR THEIR USE IN RENEWABLE ENERGY - LIASKOVETS, NAZAR; OSADTSA, YAROSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In recent years, there has been a growing trend in the use of solar and wind energy for electricity generation. This shift is primarily driven by the global need to reduce greenhouse gas emissions and combat climate change. However, the increasing share of renewable energy sources without the provision of adequate flexible generation or energy buffering, capacity may lead to a range of unforeseen technical and systemic consequences. These may include technological disruptions in the operation of the entire power grid or significant portions of it. One of the key strategies to mitigate such adverse effects is the deployment of energy storage systems. These systems enable efficient management of energy flows during the processes of generation, storage, and discharge of electricity into the grid, as well as the regulation and control of power system operations. Electrical energy storage systems are technologies designed to retain energy for later use. Each storage technology possesses unique characteristics that contribute to more efficient energy distribution and help meet demand across various energy supply sectors. Their implementation opens new opportunities for improving the quality of operational control and optimizing the performance of energy systems. This paper provides a review of the most commonly used types of energy storage systems employed in power systems and offers a comparative analysis of their key characteristics. Furthermore, an attempt is made to analyze the main categories of energy storage technologies based on their storage method, energy type, storage duration, and capacity. The findings of this study support the preliminary selection of a suitable type of energy storage system, depending on the specific characteristics and parameters of the energy system in which it is to be applied.